1992
DOI: 10.1097/00004032-199209000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Long-range Alpha Detector

Abstract: Historically, alpha-particle detectors have been limited by the very short range of alpha particles in air. This results in a number of problems inherent to alpha contamination detectors, such as relatively poor sensitivity, geometry limitations, and inefficient monitoring techniques. In this paper, we document tests of a new long-range alpha detector. The charges generated by the interaction of alpha particles with air can be transported over significant distances (several meters) in a moving current of air g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A wide range of LRAD designs may be developed, based on this general approach. MacArthur, et al, (1992b) have reported results with a LRAD configuration with a moveable source located inside a 2.4 meter-long aluminum pipe having an inner diameter of only 3.4 cm attached to the front end of an ion detector, and an air velocity of about 16 meters/& (about 2.5 s for ions to travel the length of the pipe). The ion detector output with the source located 2.4 meters from the detector was about 70% of the signal detected with the source located at the entrance to the ion detector.…”
Section: Long-range Alpha Detectormentioning
confidence: 99%
“…A wide range of LRAD designs may be developed, based on this general approach. MacArthur, et al, (1992b) have reported results with a LRAD configuration with a moveable source located inside a 2.4 meter-long aluminum pipe having an inner diameter of only 3.4 cm attached to the front end of an ion detector, and an air velocity of about 16 meters/& (about 2.5 s for ions to travel the length of the pipe). The ion detector output with the source located 2.4 meters from the detector was about 70% of the signal detected with the source located at the entrance to the ion detector.…”
Section: Long-range Alpha Detectormentioning
confidence: 99%
“…We have re-analyzed til_: ion lifetime data presented ill Ref. 3 and present some additional insights. An 8-ft-long aluminum pipe with an i.d.…”
Section: Ion Lifetimementioning
confidence: 99%
“…The radioactivity of contaminated pipes will be firstly measured to ensure the safety of operators and environment. A long-range alpha detection (LRAD) technique has been presented to measure alpha particles emitting contamination inside pipes [1][2][3][4][5][6][7]. The corresponding LRAD instrument has been developed, which consists of five units: (1) detection unit; (2) air drive unit; (3) power supply unit; (4) signal acquisition unit; (5) data processing control and display unit.…”
Section: Introductionmentioning
confidence: 99%